Formulation Development of High Strength Gel System and Evaluation on Profile Control Performance for High Salinity and Low Permeability Fractured Reservoir - Chengli Zhang; Guodong Qu; Guoliang Song (International Journal of Analytical Chemistry)
For the large pores and cracks of reservoirs with low temperatures, high salinity, and low permeability, a new type of high strength gel ABP system is developed in this paper. The defects of conventional gels such as weak gel strength, no gelling, and easy dehydration are overcome under the conditions of low temperature and high salinity. The temperature and salt resistance, plugging characteristics, and EOR of the gel system are studied. Under the condition of 32°C and 29500 mg/L salinity, the ABP system formulation is for 0.3% crosslinking agent A + 0.09% coagulant B + 3500 mg/L polymer solution P. The results show that when the temperature was increased, the delayed crosslinking time of the system was shortened and the gel strength was increased. The good plugging characteristics of the ABP system were reached, and the plugging rate was greater than 99% in cores with different permeability. A good profile control performance was achieved, and the recovery rate was improved by 19.27% on the basis of water flooding. In the practical application of the gel system, the salinity of formation water and the permeability of fractures are necessary to determine the appropriate formulation.